Infection by Diverse HIV-1 Subtypes Leads to Different Elevations in HERV-K Transcriptional Levels in Human T Cell Lines - Li, Xi; Guo, Yaolin; Li, Hanping; Huang, Xiaofeng; Pei, Zhichao; Wang, Xiaolin; Liu, Yongjian; Jia, Lei; Li, Tianyi; Bao, Zuoyi; Wang, Xiaorui; Han, Leilei; et al. (Frontiers in Microbiology, 2021)
Human endogenous retroviruses (HERVs) make up 8% of the human genome, and for millions of years, they have been subject to strict biological regulation. Many HERVs do not participate in normal physiological activities in the body. However, in some pathological conditions, they can be abnormally activated. For example, HIV infection can cause abnormal activation of HERVs, and under different infection conditions, HERV expression may be different. We observed significant differences in HERV-K transcription levels among HIV-1 subtype-infected individuals. The transcriptional levels in the HERV-K gag region were significantly increased in HIV-1 B subtype-infected patients, while the transcriptional levels in the HERV-K pol region were significantly increased in CRF01_AE and CRF07_BC subtype-infected patients. In vitro, the transcriptional levels of HEVR-K were increased 5-fold and 15-fold in MT2 cells transfected with two different HIV-1 strains (B and CRF01_AE, respectively). However, there was no significant difference in transcriptional levels among regions of HERV-K. When MT2 cells were infected with different subtypes of HIV-1 Tat proteins (B, CRF01_AE), which is constructed by lentiviruses, and the transcription levels of HERV-K were increased 4-fold and 2-fold, respectively. Thus, different subtypes of HIV-1 have different effects on HERV-K transcription levels, which may be caused by many factors, not only Tat protein.